2023
DOI: 10.5551/jat.63576
|View full text |Cite
|
Sign up to set email alerts
|

Validation of the Domestic High Bleeding Risk Criteria for Japanese Patients with Acute Myocardial Infarction

Abstract: Aims:The Academic Research Consortium (ARC) has proposed international criteria to standardize the definition of high bleeding risk (HBR) in patients undergoing percutaneous coronary intervention (PCI). In this context, Japan has also established its own guidelines, that is, the Japanese version of HBR (J-HBR) criteria. However, the J-HBR criteria have not been fully validated, especially in patients with acute myocardial infarction (MI).Methods: This bi-center registry included 1079 patients with acute MI und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
3

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 30 publications
1
7
3
Order By: Relevance
“…The discriminative abilities of the J-HBR, ARC-HBR, and PRECISE-DAPT scores for predicting major bleeding events within 1 year or more are comparable, 19 , 25 , 26 and the results of our study also showed no significant differences in the discriminative ability for predicting major bleeding events among the J-HBR, ARC-HBR, and PRECISE-DAPT scores in the time-dependent ROC curve analysis. In contrast to previous studies, 19 , 25 28 the AUC values in the present study for the J-HBR, ARC-HBR, and PRECISE-DAPT scores were higher (0.77–0.86 vs. 0.61–0.75 in previous studies). 19 , 25 28 We observed few major bleeding events in the non-HBR group according to the J-HBR and ARC-HBR scores, which may have contributed to the higher discriminative ability of those scores.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…The discriminative abilities of the J-HBR, ARC-HBR, and PRECISE-DAPT scores for predicting major bleeding events within 1 year or more are comparable, 19 , 25 , 26 and the results of our study also showed no significant differences in the discriminative ability for predicting major bleeding events among the J-HBR, ARC-HBR, and PRECISE-DAPT scores in the time-dependent ROC curve analysis. In contrast to previous studies, 19 , 25 28 the AUC values in the present study for the J-HBR, ARC-HBR, and PRECISE-DAPT scores were higher (0.77–0.86 vs. 0.61–0.75 in previous studies). 19 , 25 28 We observed few major bleeding events in the non-HBR group according to the J-HBR and ARC-HBR scores, which may have contributed to the higher discriminative ability of those scores.…”
Section: Discussioncontrasting
confidence: 99%
“…In contrast to previous studies, 19 , 25 28 the AUC values in the present study for the J-HBR, ARC-HBR, and PRECISE-DAPT scores were higher (0.77–0.86 vs. 0.61–0.75 in previous studies). 19 , 25 28 We observed few major bleeding events in the non-HBR group according to the J-HBR and ARC-HBR scores, which may have contributed to the higher discriminative ability of those scores. The reason for fewer major bleeding events in our study could be the limited use of the transfemoral approach (28% vs. 58–76% in previous studies) 19 , 25 27 and the smaller incidence of acute coronary syndrome (52.2% vs. 100% in a previous study).…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…We conducted a retrospective, bicenter registry study at 2 tertiary referral hospitals, Chiba University Hospital and Eastern Chiba Medical Center [ 13 , 14 , 15 , 16 , 17 , 18 ]. From January 2012 to March 2020, a total of 1102 patients with acute MI including ST-segment elevation MI (STEMI) and non-ST-segment elevation MI (NSTEMI) underwent primary PCI.…”
Section: Methodsmentioning
confidence: 99%
“…This was a retrospective, observational, bicenter study. [16][17][18][19][20][21] Between January 2012 and March 2020, 1,102 AMI patients I schemic heart disease, such as acute myocardial infarction (AMI), is a major underlying pathogenic factor in heart failure (HF), accounting for approximately 50% of cases in the current era, 1,2 and HF event is a strong predictor of worse outcomes among patients with AMI. 3,4 B-type natriuretic peptide (BNP) and N-terminal pro-BNP (NT-proBNP) are natriuretic peptides (NPs) secreted by the cardiac ventricles in response to end-diastolic pressure and volume, 5 and are widely used as diagnostic biomarkers for HF in clinical practice.…”
Section: Study Populationmentioning
confidence: 99%